Acheron/Larp6 Is a Survival Protein That Protects Skeletal Muscle From Programmed Cell Death During Development - Sheel, Ankur; Shao, Rong; Brown, Christine; Johnson, Joanne; Hamilton, Alexandra; Sun, Danhui; Oppenheimer, Julia; Smith, Wendy; Visconti, Pablo E.; Markstein, Michele; Bigelow, Carol; Schwartz, Lawrence M. (Frontiers in Cell and Developmental Biology, 2020)
The term programmed cell death was coined in 1965 to describe the loss of the intersegmental muscles (ISMs) of moths at the end of metamorphosis. While it was subsequently demonstrated that this hormonally-controlled death requires de novo gene expression, the signal transduction pathway that couples hormone action to cell death is largely unknown. Using the ISMs from the tobacco hawkmoth Manduca sexta, we have found that Acheron/LARP6 mRNA is induced ~1,000-fold on the day the muscles become committed to die. Acheron functions as a survival protein that protects cells until cell death is initiated at eclosion (emergence), at which point it becomes phosphorylated and degraded in response to the peptide Eclosion Hormone. Acheron binds to a novel BH3-only protein that we have named BBH1 (BAD/BNIP3 homology 1). BBH1 accumulates on the day the ISMs become committed to die and is presumably liberated when Acheron is degraded. This is correlated with the release and rapid degradation of cytochrome c and the subsequent demise of the cell. RNAi experiments in the fruit fly Drosophila confirmed that loss of Acheron results in precocious ecdysial muscle death while targeting BBH1 prevents death altogether. Acheron is highly expressed in neurons and muscles in humans and drives metastatic processes in some cancers, suggesting that it may represent a novel survival protein that protects terminally differentiated cells and some cancers from death.